PENGARUH BERCERITA KISAH ISLAMI TERHADAP KECEMASAN ANAK USIA PRASEKOLAH YANG DIRAWAT DI RUMAH SAKITSARI ASIH CIPUTAT - Dwi Sugihariyati; Indra Tri Astuti; Nopi Nur Khasanah (LPPM Universitas An Nuur, 2026)
Background: Preschool children (3-6 years old) are vulnerable to hospitalization due to their developing immune systems, which can lead to high levels of anxiety due to new environments, traumatic medical procedures, and separation from parents. The prevalence of hospitalization anxiety reaches 70.8% in South Tangerang, hindering child care and development. Therefore, non-pharmacological interventions such as Islamic storytelling, which offers positive moral values and distraction, are necessary. Objective: To determine the effect of telling Islamic stories on the level of anxiety of preschool-aged children being treated in hospital. Methods: This study used a quantitative pre-experimental study with a one-group pretest-posttest design on 15 preschool children at Sari Asih Hospital in Ciputat, using purposive sampling. The Islamic storytelling intervention (10-15 minutes/day for 3 days) was measured using the 26-item parent-reported Preschool Anxiety Scale (PAS), analyzed by the Wilcoxon SPSS test with α=0.05. Results: Before the intervention, anxiety was mild in 3 respondents (20%), moderate in 8 respondents (53.3%), and severe in 4 respondents (26.7%). After the intervention, 3 respondents (20%) experienced mild anxiety, 12 respondents (80%), and 0 respondents (0%) experienced severe anxiety. The Wilcoxon test showed a significant difference (p=0.046 <0.05), with the majority of respondents aged 3 years (6%) being female, 9 respondents (60%), and 12 respondents (80%) having experienced hospitalization. Conclusion: Telling Islamic stories effectively reduces anxiety in preschool children during hospitalization.